Public-Private Partnership Options toward Achieving Universal Health Coverage in the Philippine Setting - Eduardo P. Banzon; J.A. Lucero; B.L. Ho; M.E. Puyat; E.J. Quibod; P.A. Factor (Philippine Institute for Development Studies (PIDS), 2014)
Public-private partnerships (PPPs) are increasingly being utilized to meet development goals of many countries and there is much potential for PPPs to help address health inequities and advance universal health care (UHC). In support of these efforts, the paper defines PPPs and their role in the health system and proposes health PPP options that would support the pursuit of UHC.The objectives of this paper are to define what PPPs are and their application in the health sector. The paper presents representative case studies or models of PPP practices in health. Furthermore, it aims to provide a methodology for decisionmakers and stakeholders in developing health PPPs.
Keywords: 330; Philippines; health; public-private partnership (PPP); universal health coverage; public-private investment partnerships; public-private interactions; universal health care (UHC)